Motivation factors of football spectators' attendance on football matches / Ridhwan Sarani - Sarani, Ridhwan (Faculty of Sport Science and Recreation, 2018)
The purpose of this study to determine the specific motivation factors of football spectators' attendance on football matches based on age category and genders. A total of two hundreds spectators (N=200) were selected via convience sampling to participate in this study. This study was using demographic questionnaire and Sport Fan Motivation Scale (SFMS) questionnaire. The data were analyzing by using SPSS version 23 with two inferential statistics which were One-Way ANOVA and Independent T-Test. From the result, only one motivation factors that shown the significant differences which were escape factors (p = 0.002). Meanwhile, the motivation factors did not shown significant differences based on genders. As a conclusion, the spectators that attend to the football matches with the variety of motivation factors.